2016
DOI: 10.1093/rheumatology/kew265
|View full text |Cite
|
Sign up to set email alerts
|

Mixed connective tissue disease—enigma variations?

Abstract: In 1972, Sharp et al. described a new autoimmune rheumatic disease that they called MCTD, characterized by overlapping features of SSc, SLE, PM/DM, high levels of anti-U1snRNP and low steroid requirements with good prognosis. MCTD was proposed as a distinct disease. However, soon after the original description, questions about the existence of such a syndrome as well as disputes over the features initially described began to surface. The conundrum of whether MCTD is a distinct disease entity remains controvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 54 publications
0
29
0
7
Order By: Relevance
“…Several key features of the so-called MCTD were thus challenged casting doubt on the idea that "MCTD" was a distinct disease. Despite the claims made in the initial study, anti-RNP antibodies, even in high titre, lack specificity, the "MCTD" patients often evolve to other well-defined ARD and the idea that low-dose corticosteroid only was required was also challenged [3][4][5][6][7][8][9].…”
Section: Introduction: a Historical Perspectivementioning
confidence: 99%
“…Several key features of the so-called MCTD were thus challenged casting doubt on the idea that "MCTD" was a distinct disease. Despite the claims made in the initial study, anti-RNP antibodies, even in high titre, lack specificity, the "MCTD" patients often evolve to other well-defined ARD and the idea that low-dose corticosteroid only was required was also challenged [3][4][5][6][7][8][9].…”
Section: Introduction: a Historical Perspectivementioning
confidence: 99%
“…Mixed connective tissue disease, an autoimmune condition, which may affect almost any organ system of the body, presents with overlapping features from major connective diseases such as SLE, scleroderma, rheumatoid arthritis, dermatomyositis, and polymyositis along with an antibody against the RNP antigen [1]. Recently, a study from Norway showed an annual incidence to be 2.1 per million per year and points prevalence to be 3.8 per 100,000 indicating that MCTD is the least common connective tissue disorder [2].…”
Section: Discussionmentioning
confidence: 99%
“…Mixed connective tissue disease (MCTD), first described in 1972 by Sharp, represents an overlapping disease of different autoimmune conditions such as systemic lupus erythematosus (SLE), scleroderma, rheumatoid arthritis, polymyositis, and dermatomyositis that often exist with antibodies targeted towards the U1 small nuclear ribonucleoprotein (RNP) autoantigen [1]. MCTD or Sharp syndrome is usually considered incurable and presents with a broad spectrum of symptoms such as Raynaud's phenomenon, swollen fingers, erosive arthritis, sclerodactyly along with pulmonary and central nervous system involvement [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to ascertain whether patients’ disease is truly undifferentiated or represents an overlap syndrome as such antibodies may also be seen in patients with SLE, SSc or polymyositis . Currently, four coexisting classification criteria for MCTD exist which further complicate establishing a diagnosis . Presence of anti‐U1 ribonucleoprotein antibody immunological marker, Raynaud's phenomenon, joint involvement and muscle involvement exist across all four classifications .…”
Section: Mixed Connective Tissue Diseasementioning
confidence: 99%